A Case Study Analysis of the “Letter from Birmingham Jail”: Conceptualizing the Conscience of King through the Lens of Paulo Freire - Tremaine T. Sails-Dunbar (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2017)
The pedagogical qualities of Martin King’s “Letter from Birmingham Jail” can be observed through the lens of Paulo Freire as his illustration of thematic universe’s can be used as a framework to contextualize the conscience of King. King encountered obstacles, in his contemporary context, to his self-actualization that once cognitively subjugated were transformative to his being. Three questions are explored: What manifestations led to the writing of the “Letter from Birmingham Jail”? What were King’s transformative actions? Will an answer to the first help make sense of the second? I endeavor to briefly examine the “Letter from Birmingham Jail” through the lens of Paulo Freire.
Keywords: Obstacles To Liberation; Project C; Martin Luther King And Paulo Freire; Birmingham; Thematic Universe; Why We Can’t Wait; Pedagogy Of The Oppressed; Segregation